1993
DOI: 10.1104/pp.102.4.1227
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Induced Changes in Freezing Tolerance, Protein Phosphorylation, and Gene Expression (Evidence for a Role of Calcium)

Abstract: l h e role of Ca'+ in cold-induced changes i n protein phosphorylation, gene expression, and development of freezing tolerance has been studied in cell-suspension cultures of a freezing-tolerant cultivar of alfalfa (Medicago safiva spp. falcafa cv Anik). Chemical treatments to block Caz+ channels, antagonize calmodulin action, or inhibit protein kinases markedly inhibited the cellular capacity to develop cold-induced freezing tolerance but had little effect on cell viability. An analysis of phosphoprotein prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
184
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(200 citation statements)
references
References 23 publications
11
184
1
Order By: Relevance
“…Isolation of CRLK1-interacting proteins/substrates will help in further dissecting this signal pathway. Accumulating evidence indicates that protein phosphorylation is involved in the pathway connecting the cold-triggered calcium changes and cold acclimation (22,39). However, the protein kinase(s) responsible for inducing cold-regulated genes and activating freezing tolerance is elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of CRLK1-interacting proteins/substrates will help in further dissecting this signal pathway. Accumulating evidence indicates that protein phosphorylation is involved in the pathway connecting the cold-triggered calcium changes and cold acclimation (22,39). However, the protein kinase(s) responsible for inducing cold-regulated genes and activating freezing tolerance is elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, the rapid influx of calcium into the cytosol is required for normal cold induction of the CBF target genes KIN1 and KIN2 (Knight et al, 1996;Tahtiharju et al, 1997). Similarly, in alfalfa, cold-induced accumulation of transcripts for two coldresponsive genes, cas15 and cas18, is dependent upon calcium (Monroy et al, 1993;Monroy and Dhindsa, 1995).…”
Section: Linking Calcium Signaling To Cold-regulated Gene Expressionmentioning
confidence: 99%
“…Nearly 20 years ago, Knight et al (1991) established that exposure of plants to low temperature results in a rapid transient spike in cytoplasmic calcium levels. Subsequent studies linked the cold-induced calcium spikes to cold-regulated gene expression in Arabidopsis (Knight et al, 1996;Tahtiharju et al, 1997;Henriksson and Trewavas, 2003) and alfalfa (Medicago sativa; Monroy et al, 1993;Monroy and Dhindsa, 1995). For instance, the studies with Arabidopsis demonstrated that chemical agents that reduce calcium influx into the cytoplasm impaired cold induction of certain CBF regulon genes.…”
Section: Upstream Of the Cbf Regulatory Hub: Sensing Low Temperature mentioning
confidence: 99%